Winter CO2 Efflux From Sagebrush Shrublands Distributed Across the Rain‐to‐Snow Transition Zone. Issue 2 (24th February 2020) - Fellows, Aaron W.; Flerchinger, Gerald N.; Seyfried, Mark S.; Biederman, Joel A.; Lohse, Kathleen A.
Abstract: The projected shifts in winter weather and snowpack conditions are expected to impact carbon storage in western U.S. rangelands. Sagebrush shrublands comprise much of the western United States, yet contribution of winter CO2 efflux to the overall carbon budget of these ecosystems remains uncertain. We explored factors controlling winter CO2 efflux measured using eddy covariance at five sagebrush‐dominated sites along an elevation/climate transect extending from 1, 425 to 2, 111 m. Results showed that winter CO2 efflux was modest but had important impacts on annual carbon budgets, and its impact increased in high‐elevation, snow‐dominated ecosystems compared to low, rain‐dominated ones. Observed cumulative winter CO2 efflux accounted for 8–30% of annual gross ecosystem production (GEP) and roughly approximated annual net carbon uptake. Omission of winter periods would have increased net uptake by 1.5 to 2.2 times. Within‐site variability in observed 30‐min winter CO2 efflux was related to soil temperature and moisture. Between‐site variability was attributed to available carbon stocks, including soil organic carbon and the previous year's GEP. At low elevations, lack of snow cover to insulate soil from freezing, coupled with lower carbon stocks, limited CO2 efflux. Conversely, large carbon stocks and deep snowpack that prevented soil freezing at high elevation led to increased CO2 efflux. These results show how climate and biota exert strong controls on winter ecosystem respiration and extend our understanding of how state factors influence winter CO2 efflux. Collectively, our findings suggest that an upward climatic shift in the rain‐to‐snow transition elevation may alter the carbon budget of sagebrush shrublands. Plain Language Summary: Climate warming and associated shifts in winter precipitation from snow to rain are expected to affect wintertime plant and soil respiration, impacting carbon cycling and storage. Sagebrush shrublands comprise much of the western United States, yet the contribution of winter CO2 emission from these ecosystems is uncertain, even under current conditions. We therefore examined winter ecosystem respiration and explored factors controlling CO2 emission from five sagebrush sites with varying elevation, snow, and winter conditions. Factors controlling CO2 emission were shown to change with elevation. Limited CO2 emission was observed at low‐elevation sites due to lack of snow cover to insulate the soil from freezing, limited water availability, and low soil organic content. Conversely, high soil organic content and a deep snowpack that prevented soil freezing at high elevation led to increased winter CO2 emission that resulted from higher rates of respiration and organic decomposition. Results suggest that anticipated reductions in snow depth with climate warming may lead to colder winter soil temperatures, increased freezing, and therefore reduced winter respiration and CO2 emission. Key Points: Factors controlling winter CO2 efflux were shown to change with elevation Large carbon stocks and a deep snowpack that prevented soil freezing at high elevation led to increased CO2 efflux An upward climatic shift in the rain‐to‐snow transition elevation may enhance carbon sequestration of sagebrush shrublands